The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1039/b301388j
|View full text |Cite
|
Sign up to set email alerts
|

Ion–soot interaction: a possible mechanism of ion removal in aircraft plume

Abstract: The phenomenon of the ion-soot interaction in the aircraft plume at the ground conditions is investigated. The ion-soot attachment coefficients, taking into account the polarization of the soot particles in the ion electric field, are calculated. It is shown that the ion-soot attachment may play the important role in the evolution of the ion concentrations in the plume. Comparison of the model results with the ground-based measurements for the ion depletion along the plume demonstrates that the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The character of ion−soot interaction strongly depends on the electrical properties of the soot particles. Our soots feature conductivities that imply charge delocalization on the surface . This means that the ion−soot interaction is dictated by both Coulomb and image forces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The character of ion−soot interaction strongly depends on the electrical properties of the soot particles. Our soots feature conductivities that imply charge delocalization on the surface . This means that the ion−soot interaction is dictated by both Coulomb and image forces.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, attachment coefficients should be increased when taking into account the image capture trapping . Attachment coefficients of ions to kerosene soot particles were calculated in Popovicheva et al We can estimate to 5−45 h the characteristic time of the ion concentration reduction at the zonal mean perturbation of soot concentrations of ∼3−30 cm -3 . As a consequence, that may result in a significant reduction of the electrical ionic conductivity in the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown (see, for example, Place & Weinberg, 1966;Ball & Howard, 1971;Wersborg, Howard, & Williams, 1973;Onischuk et al, 2003;Burtscher, Reist, & Schmidt-Ott, 1986;Roth & Hospital, 1994;Popovicheva, Persiantseva, Starik, & Loukhonitskaya, 2003;Sorokin, Vancassel, & Mirabel, 2003) that soot aggregates formed in combustion are charged as well as ame generated inorganic aggregates (see, for example, Katzer, Weber, & Kasper, 2001). The soot aggregate charge arises from bipolar ion di usion in the reaction zone (Calcote, 1981;Calcote & Gill, 1994;Burtscher et al, 1986;Rogak & Flagan 1992;Wen, Reischl, & Kasper, 1984a;Alonso, Hashimoto, Kousaka, Higuchi, & Nomura, 1998;Fuchs, 1964).…”
Section: Introductionmentioning
confidence: 96%
“…This model involves the block of reactions describing the combustion of high-order hydrocarbons C n H 2n+2 (n=1…10) with air, production of S-containing species caused by the oxidation of fuel sulfur, and generation of various positive and negative ions (electrons) (Starik et al, 2002). Recent investigations (Popovicheva et al, 2003) have demonstrated that engine-generated soot has rather high electroconductivity. Hence, the particles turn out to be polarized in the ion-produced electric field and to compute the ion-soot attachment coefficients we should take into account the exerting both Coulomb and image forces.…”
Section: Methodology and Resultsmentioning
confidence: 99%